Der Kampf um Chinas kollektives Gedächtnis Offizielle und inoffizielle Narrative zur Kampagne gegen Rechtsabweichler (1957-58) - Blanke, Anja (De Gruyter, 2021)
Since the death of Mao Zedong in 1976, the Chinese Communist Party has been fighting for an inner-party and societal consensus on how to deal with its own "historical mistakes." Anja Blanke shows that the battle for collective memory is one of the ongoing, central political challenges facing the CPC as it seeks to stabilize the legitimation of its rule.